The Impact of COVID-19 Pandemic on Egypt’s Tourism. New Challenges for Media Houses to Make Awareness for Safety to Travel - ALASHRY, Miral Sabry; ALKHUDARI, Majid (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
The purpose of this study is to analyze the impact of the acceptance of national governments’ restrictions imposed due to the COVID-19 pandemic on the Egyptian citizens’ safety perceptions of daily life and the future. Questionnaire 244 from Egyptian citizens. To identify the factors underlying the ‘‘acceptance of restrictions and measures’’ and the ‘‘Impacts of the COVID-19 threat on safety perceptions in 2021 to know the acceptance of restrictions to return to travel again after being vaccinated. The results reveal that in general, young generations accepted the measures and restrictions imposed by the respective governments and they accepted vaccination to return to travel.  The originality of the study to the knowledge, besides the relevant studies already conducted on the impact of the COVID-19 crisis in the tourism field after the young generations, were vaccinated.